Addressing the issue of mixed-ability students in CLT classrooms using self-check politeness kit / Suryani Awang … [et al.] - Awang, Suryani; Wan Zakaria, Wan Nuur Fazliza; Razak, Siti Shazlin; Ibnul Hakim Saad, Muhammad Luqman; Mohd Zawawi, MMohd Zafian (Universiti Teknologi MARA, 2018)
After more than three decades of its adoption in the English language teaching in Malaysia, Communicative Language Teaching (CLT) approach is yet to prove its effectiveness in this country since the English competency level among Malaysian students is reported to be gradually declining among our students and fresh graduates. One common cited reason is they lack competency in using the English language. Nevertheless, CLT should help to enhance learners’ communicative competence if this teaching approach is ideally conducted in L2 classrooms. This includes learners’ ability to employ politeness strategies in oral interactions. In this regard, past studies have shown that students with different English language competency level tended to employ different politeness strategies, hence resulting in different politeness levels displayed during oral interactions. While some strategies can lead to successful communication, others might appear inappropriate. Hence, this scenario could be seen as a threat in L2 learning. Despite this however, the teaching of appropriate politeness strategies among students of mixed-ability in CLT classrooms can be a great help. Here, input on appropriate politeness strategies from more proficient and competent students who are usually more polite is extremely important for less competent classmates to improve their politeness level. This is the concept behind the introduction of Self-Check Politeness Kit (S-CP Kit).